Comparison of Microclimate Condition and Thermal Comfort Levels between Public and Private Green Open Space: A Case Study of Denggung Park and Gadjah Mada University Wisdom Park - Ghaniyy, Abi Abdillah Niko; Ningrum, Diah Fitri Astuti (Jurnal Ilmu Kehutanan, 2025)
Rapid urban population growth has driven extensive economic, residential, educational, and cultural development, leading to the conversion of green spaces into built-up areas. This conversion interferes with the regulations of air temperature and Thermal Humidity Index (THI). This research investigated the characteristics of green open spaces at Denggung Park and Gadjah Mada University Wisdom Park, examining their effects on microclimate conditions and the relationship between green space conditions and THI levels. The methods included a literature review, field measurements of vegetation and microclimate variables, tree crown profile analysis using Sexl-FS, and Spearman Rank Correlation. Results showed that tree density has a direct relationship with THI. The private green space (Wisdom Park), with 126.33 trees/ha, achieved superior THI compared to the public space (Denggung Park), with 49.01 trees/ha. The Gadjah Mada University Wisdom Park's more complex canopy structure and optimal canopy connectivity significantly enhanced THI. Spearman Rank Correlation analysis revealed strong relationships between the tree density and thermal comfort level for Denggung Park (-0.52) and for Gadjah Mada University Wisdom Park (-0.69), with a p-value < 0.05. These findings confirm the critical importance of optimizing vegetation structure and density to support thermally comfortable urban environments.